Attenuation of thermal radiation through water mist. Issue 1 (7th July 2017) - Balner, Dalibor; Barcova, Karla
Abstract : This article focuses on the interaction of thermal radiation with water droplets and the creation of water mist for the purpose of evaluating the decrease of heat flux when positioning a water curtain of various parameters between a radiation source and a radiometer. The change of water curtain parameters, affecting the passing through of thermal radiation, was performed using five nozzles with a variable spray characteristics. For the respective nozzles the attenuation of thermal radiation was determined and the thermal radiation transmittance was calculated. Water mist was created using a high‐pressure pump and nozzles with a different size of the orifice. The measurement of droplet size was performed using the time‐shift technique. The Omegalux radiant panel was used as the radiation source and the Hukseflux SBG01 radiometer with a working range of 0–5 kW.m −2 was used as the detector. © 2017 American Institute of Chemical Engineers Process Process Saf Prog 37:18–24, 2018